Assessment of Organizational Maturity for Lean Change - Tortorella, Guilherme Luz (2013)
Theimplementation of Lean Production Systems (LPS) is admittedly essential forcompanies that want to obtain high level of competitiveness. However, besidesthe technical factors, the LPS implementation depends heavily on theorganizational learning (OL) factors, which support and provide sustainabilityfor the organizational lean change. This article aims to present a method for forassessing the impact of OL problems on each lean implementation roadmap phase. Theproposed method complements an existent methodology through the addition of theQFD reverse calculation step. This complementary approach allows companiesunder lean implementation to identify and anticipate future problems, as wellas understand which phases are most affected by deficiencies in OL issues. Themethod is illustrated on an autoparts company, which has been in leanimplementation process for more than nine years and still presents difficultiesin sustaining the LPS.